Place of performance : a comparative analysis - Okoli, Chukwuma Samuel Adesina (London [England] : Hart Publishing, 2020)
"This book provides an unprecedented analysis on the place of performance. The central theme is that the place of performance is of considerable significance as a connecting factor in international commercial contracts. This book challenges and questions the approach of the European legislator for not explicitly giving special significance to the place of performance in determining the applicable law in the absence of choice for commercial contracts. It also contains, inter alia, an analogy to matters of foreign country mandatory rules, and the coherence between jurisdiction and choice of law. It concludes by proposing a revised Article 4 of Rome I Regulation, which could be used as an international solution by legislators, judges, arbitrators and other stakeholders who wish to reform their choice of law rules."--
II. Proposed Model of a Revised Article 4 of Rome I Regulation and Accompanying Recitals -- III. Alternative Proposal -- 7. Conclusion -- I. Summary of the Research Findings -- II. Transmission of the Model of the Revised Article 4 of Rome I Regulation to Other Countries or Legal Systems -- III. Final Word -- Bibliography -- Index
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: European Parliament; Conflict of laws -- Contracts -- European Union countries; Private international law & conflict of laws; Electronic books